Yuan Versus United States Dollar: the Defective Bipolar China–United States Relationship - Smagorowicz-Chojnowska, Małgorzata (International Studies. Interdisciplinary Political and Cultural Journal, 2018)
The chosen currency regime places a state within the international economic order. Therefore, the exchange rate is a key to creating an internal financial system and opening it up to foreign participants. In this paper we would like to show the differences between China and the USA and examine their impact on potential changes on the distribution of power in the international system. We will also try to prove that this field is a missing link in preventing the final launching of a symmetrical bipolar system which will finally force China to accept the rules of a Washington Consensus instead of following its own patterns. The case study method will be used in order to compare market data and assess the role of currencies for the given model.